A Literature Review of Mergers and Acquisitions - NIRMALA, Dr.S.; G, ARUNA (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
An extensive review of literature has been carried out in order to get a good understanding in the topic of Mergers and Acquisitions. Literature review has been done from books, journal, published papers etc.The issues covered include Motives, Share value creation, Financial performance, operating performance. These studies have been reviewed and presented in the following manner. Literature review has been collected from both within India and outside India.